Impediments of Hyphenated Identity in Zadie Smith’s The Autograph Man - T Anisha,; T Subitha, (International Journal of Psychosocial Rehabilitation, 2020)
Zadie Smith is a reputed young British writer famous for her novels, essays and short stories. The Autograph Man (2002) the second novel by Zadie Smith has established a fantastic Universal outstriks in North West London,which is ridiculously known as Mountjoy. It is a version of loss ,delusion, mixed- race and won that 2003 Jewish Quarterly Literary Prize for fiction. The Autograph Man is a sentimental novel than any other works of Zadie Smith. The character Alex, a Chinese -Jewish -British hero resembles a Jewish and a Chinese in his eyes and relatively British belonging and not associated to any humanity or culture as a whole. This novel confronts barriers of identity escalating between Jewish, British and Chinese identities . It is investigated as the course to an exalted sense of self-knowledge and valued in an affirmative tone. Alex will consistently have his Chinese eyes, but not a kitty Alexander Obsession. He used to follow Jewish rituals when it is necessary but not assuming in them. On the basis of Smith's humorous consequence the text portrays a specific sentiment towards the future and not giving a solution for approaching cultural riots